Diuresis Effect Comparison between Leaf Extract of Orthosiphon aristatus and Hydroclorotiazidto Male White Rat (Rattus novergicus) - HERWANLISTANTO, ANGGIE; Ediningsih, Endang; Maârufah, Siti (Nexus Biomedika, 2017)
Introduction: Kumis kucing leaf containing flavonol which can generate diuresis effect with increasing the excretion of natrium and chlorine. The purpose of this research was to know how did the diuresis effect of kumis kucing leaf extrack compared to hydroclorotiazid. Methods: The research was a laboratory experimental analytic study with posttest only control group design. The research subject was a number of 30 male white rats of wistar strain, aged about 2-3 months old and 150-200 grams of weight, which divided into five treatment groups. Group 1was given 2 ml CMC 1% as negative control, group 2 was given 0.32 mg hydroclorotiazid in 2 ml aquadest as positive control, group 3 was given kumis kucing leaf extract dose I (50 mg in 2 ml CMC 1%), group 4 was given kumis kucing leaf extract dose II (100 mg in 2 ml CMC 1%), group 5 was given kumis kucing leaf extract dose III (200 mg in 2 ml CMC 1%). Rats urine volume was measured every 6 hours for 24 hours observation. Result:The average measurements of rat urine volume for 24 hours showedthat group negative control had average volume3.387±1.435 ml, the average volume of positive control was7.307±0.607 ml,the average volume group dose I was 2.900±0.350 ml, the averagevolume group dose II was 3.490±0.311 mlanddose III had average volume 5.433±0.641 ml. Result of anova statistical calculation showed there are significant difference urine volume in those five groups (p <0.05). Conclution:The research conclude that kumis kucing leaf extract had diuresis effect lower than hydroclorotiazid therapeutical dose. Keyword: kumis kucing leaf extract, hydroclorotiazid, diuresis